(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In general, it is not possible to complete the delivery of the package competently because the main challenge is insufficient smart technology to identify the user for a package authentication. Therefore, fingerprint authentication is one of the intelligent authentication ideas of the package used as one solution to the above reference problem. The model should be properly prepared with regard to behavioral design in order to incorporate the UAV transport system in cities. The drone activity preparation and fingerprint authentication model for providing solutions is suggested in this regard. In terms of the computing time of the UAV and the optimality difference, the experimental results indicate a feasible solution and provide an efficient solution model.